A fuzzy cognitive map approach to predict the hazardous effects of malathion to environment (air, water and soil). (January 2021) - Poomagal, S.; Sujatha, R.; Kumar, P. Senthil; Vo, Dai-Viet N.
Abstract: Malathion is an organophosphorus insecticide and pesticide commonly used in crops and residential applications. The negative effects of Malathion on human health and ecosystems are of great concern. In this work, a mathematical model pivot on Fuzzy Cognitive Map (FCM) is used to analyse the causes and hazardous effects of Malathion to the environmental components (air, water and soil). Based on expert's opinion the possible factors that cause damage to health and ecosystems due to Malathion is identified, which serve as the input to the FCM. The FCM mathematically establishes the causal relation between these factors. The mathematical simulation is done by Python Programming. This approach can be used to study the interdependencies between the adverse effects of any pesticide in human health and environment due to prolonged exposure. Highlights: The factors affecting the environment due to Malathion was identified through experts. A mathematical model pivot on Fuzzy Cognitive Map was used to analyse the impact of Malathion to environment. Mathematical simulation was carried out by using Python Programming. Identified the interdependencies of the adverse effects of pesticides to the environment due to prolonged exposure.